2022
DOI: 10.1002/hbm.26038
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic brain activity patterns across large‐scale networks predict reciprocity propensity

Abstract: Reciprocity is prevalent across human societies, but individuals are heterogeneous regarding their reciprocity propensity. Although a large body of task-based brain imaging measures has shed light on the neural underpinnings of reciprocity at group level, the neural basis underlying the individual differences in reciprocity propensity remains largely unclear. Here, we combined brain imaging and machine learning techniques to individually predict reciprocity propensity from resting-state brain activity measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 117 publications
0
1
0
Order By: Relevance
“…Alternatively, data-driven quantitative reasoning studies suggest that SN and CEN facilitate individuals to build long-term social relationships through emotional processing and cognitive control and that DMN facilitates individuals to develop long-term social relationships through mentalizing processes. It has been suggested that it predicts the experiences, beliefs, and intentions of others and facilitates interaction (Li et al, 2022). In particular, DMN has been implicated in both functional and structural studies as prosocial personality traits such as extraversion and agreeableness (Mars et al, 2012;Sampaio et al, 2014;Coutinho et al, 2013), and it is associated with self-cognitive empathy (Silva et al, 2018;Esménio et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, data-driven quantitative reasoning studies suggest that SN and CEN facilitate individuals to build long-term social relationships through emotional processing and cognitive control and that DMN facilitates individuals to develop long-term social relationships through mentalizing processes. It has been suggested that it predicts the experiences, beliefs, and intentions of others and facilitates interaction (Li et al, 2022). In particular, DMN has been implicated in both functional and structural studies as prosocial personality traits such as extraversion and agreeableness (Mars et al, 2012;Sampaio et al, 2014;Coutinho et al, 2013), and it is associated with self-cognitive empathy (Silva et al, 2018;Esménio et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent neuroscience findings have shown that emotion states are not only encoded in spatial-spectral-temporal EEG features but also encoded in functional network connectivity such as the covariance and coherence among different brain signal channels [22], [23]. Moreover, the brain circuits encoding emotions distribute across multiple frontal-limbic brain regions that have reciprocal functional interactions [24]- [27]. Therefore, directly using whole-brain EEG network connectivity for emotion recognition can be a promising approach.…”
Section: Introductionmentioning
confidence: 99%